In search of alternative policing : Kylemore Neighbourhood Watch, the protectors of their beloved community - Visser, Cassandra (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2009.